(untitled) (Journal of history-rus, 2022)
The article examines the letters of the prominent thinker of medieval muslim renaissance to Kazakhstan and Central Asia Abu Nasr al-Farabi with the first congregator, the first pharabiologist Akzhan al-Mashani with the imam-scientist, who in the early 60s of the XX century kept the path of religion and science on an equal footing to the people of Kazhibay Mandibaiuly, a copy of the manuscript of imam-scientist Kazhibay Mandibaiuly «On the foundations of nature science, which was high» («Zhogary bolgan tabigat gylymynyn negіzderі zhaiynda»). The first scientific research on the farabiology of the scientist Akzhan al-Mashani was released in the 50s of the XX century. As he notes in his work «Al-Farabi and Abai» in 1994 and in the research article «Nurnama Al-Farabi» which published in 1994 in No.2 of the popular science magazine of «Zerde», with the helped of the famous kazhi Saduakas Gylmani, he met with the arabic-speaking imams-mullahs Gabbas Otarluly, Rahim Sarsenuly and Kazhybai Mandybayuly, and later with their help began to study the heritage of al-Farabi. This article consists of the results of the scientific visit of the aspirant from especially valuable documents from the fund of the local historian Kasenov Aydarzhan Baltabaiuly, who mastered the kadym reading, chagatai, sulu zhadid.